2021
DOI: 10.20895/infotel.v13i4.712
|View full text |Cite
|
Sign up to set email alerts
|

Designing a microcontroller-based half-duplex interface device drove by the touch-tone signal

Abstract: The interface device for communicating (IDC) as a bridge for the merger between two different systems based on different protocols and standards can be made of several electronic modules. The two Arduino boards (UNO R3 and MEGA2560 R3) have been constructed as the electronic modules of a gateway become a haft-duplex IDC, and are driven by the touch-tone signal. The research objectives, i.e., assembling some of the hardware for the embodiment of the adapter system, making a program structure, and performing a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The research method is an algorithm of a researcher for conducting the research that is carried out in the form of stages for achievement and accordance with the objectives of research [38][39][40][41]. The flowchart of the research methods is shown in Figure 1.…”
Section: Methods Of the Researchmentioning
confidence: 99%
“…The research method is an algorithm of a researcher for conducting the research that is carried out in the form of stages for achievement and accordance with the objectives of research [38][39][40][41]. The flowchart of the research methods is shown in Figure 1.…”
Section: Methods Of the Researchmentioning
confidence: 99%
“…The methods of research are an algorithm of a researcher for conducting the research that is carried out in the form of stages to achievement and which is guided by the research objectives [41], [25]. In other words, some stages must be carried out sequentially the objectives [41], [42], [25], [26], [43] so this research method is made in the form of a flow chart, and under steps for achieving each research objective [42], [26], [43]. The flowchart of the research methods is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…It ranges from common consumer electronic devices to home, office, factory or industry applications and automotive and avionic implementations [22]. Using a microcontroller-based electronic module that is manufactured as desired [23], [24] or direct service the board of Arduino [25], [26] as a control system for many purposes has been used become a certainty.…”
Section: Introductionmentioning
confidence: 99%
“…The ideas and activities of this research are based on previous research which has been published [1,2], namely (i) an electronic device reviewed by diagnosing the embodiment of the module [1] and (ii) designing a microcontroller-based half-duplex interface device driven by the touch-tone signal [2], therefore this research is a follow-up activity in the form of observing the performance of the equipment after the verification tests have been carried out in the previous article [2]. The final result comes from manufacturing or assembling and is an integral part of the new product or product development process are require verification and validation tests [3].…”
Section: Introductionmentioning
confidence: 99%
“…The radio-based communication system is known as a radio communication system (RCS) or radio-frequency system (RFS) [12][13][14][15], whereas the telephony-based communication system is known as a public switched telephone number (PSTN) or global system for mobile communication (GSM) [16][17][18][19][20]. The connecting device is better known as the IDC and the term interface device for communicating (IDC) is previously known as communication interface adapter (CIA) [1,2]. The stage of the verification test has been published with the product design against its specifications [4].…”
Section: Introductionmentioning
confidence: 99%